Origin of zeolites from the Kirkpatrick basalt, Solo Nunatak, Antarctica: significance to the petrogenesis of basalt - Mason, Scott E. (The Ohio State University, 1984)
The Kirkpatrick Basalt has an anomalously high initial 87Sr/86Sr ratio which varies from 0.709 to 0.714. One possible cause for the Sr isotopic anomaly is the alteration of the basalt by the solutions which precipitated zeolites in the vesicles of the basalt. In this study, zeolites from the Kirkpatrick Basalt of Solo Nunatak, North Victoria Land, Antarctica, were found to have identical initial 87Sr/86Sr ratios (0.7100 to 0.7105) as the Kirkpatrick Basalt flows in which they occurred. Therefore, the zeolites formed soon after crystallization of the basalt with Sr derived from the basalt. Because the Sr of the zeolite-forming solutions was derived from the basalt, the Sr isotopic composition of the basalt was not altered by the zeolite-forming solutions. No embargo